Pengaruh Media Pictorial Health Warning Terhadap Motivasi Merokok Pada Remaja - Pipit Festi Wiliyanarti; Hikmatul Hasanah; Gita Marini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Smoking is a dangerous behavior for health, which is still widely practiced, especially among adolescents. Problem that occur in adolescents one of which is the lack of motivation to stop smoking. Pictorial Health Warning is one of the Health Promotions that can influence smoking behavior. The purpose of this study was to analyze the effect of Pictorial Health Warning on smoking motivation in teens at Surabaya Mujahidin Middle School.This study uses a pre-experimental design with one group pre-test-post test design. The population in this study were all male smoker students in Surabaya Mujahidin Middle School. The sampling technique used was total sampling so that 45 students became respondents in this study. The independent variable is Pictorial Health Warning in cigarette packaging. The dependent variable is motivation on the incidence of teenage smoking. Data were collected using an observation sheet and then analyzed using the Wilcoxon Sign Ranks Test with a significant level <0.005.The results showed that the effect of Pictorial Health Warning on smoking motivation, there was a significant effect on motivating smoking behavior (p = 0,000) on adolescents. Media Pictorial Health Warning can be used as a medium in health education for adolescents to reduce motivation to smoke.